Minocycline as a therapeutic strategy against the brain dysfunctions induced by hypercholesterolemia. (December 2021) - Martins, Julia Nostrani; Rodrigues, Matheus Scarpatto; Farias, Hemelin Resende; Fossá, Matheus Henrique Rossoni; Schons, Tainá; Budni, Josiane; de Bem, Andreza Fabro; de Oliveira, Jade
Abstract: Background: About 40% of adults have elevated plasma cholesterol levels, making hypercholesterolemia a critical health issue. Clinical and experimental evidence have shown that hypercholesterolemia contributes to the development of neuropathologies. Mechanisms such as blood‐brain barrier dysfunction and neuroinflammation seem to connect hypercholesterolemia to brain changes related to these neuropathologies. Minocycline, an antibiotic compound of the tetracycline class, has shown significant neuroprotective effects in experimental studies, particularly on the inhibition of microglial activation. In this sense, we hypothesized that minocycline could display beneficial effects in the cognitive deficits related to hypercholesterolemia. Method: In this study, CF‐1 male and female adult young (3 months old) mice were treated with either a standard diet or a high cholesterol diet (2.5% of cholesterol). After four weeks, the animals also received minocycline or 0.9% saline by oral gavage once a day for another four weeks, totaling eight weeks of the experimental period. Next, the animals were subjected to behavioral tests, such as object recognition, splash test, and cataleptic posture. After that, the glucose tolerance test was performed, and the plasma was collected for the further performance of the biochemical analysis. Result: Eight weeks of high cholesterol diet consumption caused an increase in the total plasma cholesterol levels of animals, which were reduced by the treatment with minocycline. Both diet and minocycline did not affect the plasma glucose levels and the glucose tolerance of animals. Also, hypercholesterolemic mice exhibited a higher body weight, weight gain, and adiposity index at the end of the experimental period. However, these parameters were not affected by the minocycline treatment. Regarding the behavioral tests, hypercholesterolemia in mice was related to a significant deficit in recognition memory and cataleptic posture, which were improved by minocycline treatment. In addition, hypercholesterolemia induced depressive‐like behavior in mice, reflected by less grooming time on the splash test, which was not changed by the minocycline treatment. Conclusion: Therefore, our results show that administration of minocycline presented promising effects in ameliorating the cognitive and behavioral deficits related to hypercholesterolemia, demonstrating that microglial activation might play a role in the memory deficits induced by this metabolic disease.